How power-sharing includes and excludes non-dominant communities: Introduction to the special issue. Issue 1 (January 2020) - Agarin, Timofey; McCulloch, Allison
As the introduction to the special issue titled Democratisation in Divided Places: Designing Power-Sharing Institutions for Broad Inclusion, this article situates the themes, issues, and findings of the issue in a broad disciplinary perspective. Drawing from theories of constitutional design, peacebuilding, democratisation, and ethnonational accommodation, the article outlines the trade-offs that power-sharing faces in war-to-peace transitions and the implications for non-dominant groups. We articulate what we see as a central problem with contemporary power-sharing arrangements, a phenomenon we call the 'exclusion amid inclusion' dilemma. That is, for power-sharing to create stability and pacify the dominant groups, it must marginalise non-dominant groups. These are groups who were neglected in the original design of power-sharing institutions, who remain on the sidelines of postconflict politics, and who face major institutional constraints on their representation and participation in the power-sharing arrangement. Using 'exclusion amid inclusion' as an analytical lens, we explain how the articles included in the special issue highlight how different societies have grappled with the question of facilitating broad inclusion in the design of political power-sharing institutions.